From Na+/K+-ATPase and Cardiac Glycosides to Cytotoxicity and Cancer Treatment - Babula, Petr; Masarik, Michal; Adam, Vojtech; Provaznik, Ivo; Kizek, Rene (Anti-Cancer Agents in Medicinal Chemistry, 2013)
The cardiac glycosides are a group of compounds isolated from plants and some animals. They have been used in therapy for heart failure for many years. The cytotoxic effect of many cardiac glycosides has been demonstrated, but the mechanism of action is very complicated and complex, and Na+/K+-ATPase surely plays a crucial role in it. On the other hand, Na+/K+-ATPase is regulated by many endogenous factors, such as hormones or FXYD proteins, whose role in regulating the cell cycle has been studied intensively. This review focuses on the role of Na+/K+-ATPase in regulating the cell growth, the cell cycle and the cell proliferation and on the involvement of cardiac glycosides in regulating Na+/K+-ATPase. The cytotoxic effect of cardiac glycosides is discussed with respect to the apoptotic mechanisms possibly induced by these compounds. Novel strategies in cancer therapy based on cardiac glycosides are discussed as are possibilities for counteracting multidrug resistance by using cardiac glycosides. The aim of this review is to present cardiac glycosides not only as pharmaceuticals used in the management of heart failure, but also as potent cytotoxic agents with potential uses in cancer treatment.
Keywords: Cardiac glycosides